Permainan Crossword Puzzle untuk Meningkatkan Aktivitas dan Hasil Belajar PKn Materi Sumpah Pemuda pada Siswa Kelas III SDN 1 Sidowayah Polanharjo Klaten Semester I Tahun Pelajaran 2018/2019 - Sri Purwaningsih (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this study was to find out: (1) Activity of students in Civics learning material in the system of regency, city and provincial government with crossword puzzles in class III SD Negeri 1 Sidowayah Polanharjo Subdistrict, Klaten District 2018/2019 (3) Student learning outcomes in Civics learning material in the regency, city and provincial government system with crossword puzzles in class III SD Negeri 1 Sidowayah Polanharjo Subdistrict, Klaten District 2018/2019. This type of research is Classroom Action Research (CAR), with research procedures: planning, action, observation, and reflection. Data collection techniques use: observation, tests, interviews, and documentation. The results of the study concluded: (1) Civics learning with crossword puzzles (TTS) increases the active involvement of students during learning, and increases student learning enthusiasm. Students feel happy, and can learn to cooperate constructively and respect each other in group learning. The activities of teachers in Civics learning with crossword puzzles (TTS) do not dominate the learning process. The teacher has more role as: motivator, which is a lot of motivation for students; mediator namely mediating between students when the discussion takes place; and the facilitator is giving direction to students when learning takes place; (2) Civic learning with crossword puzzles (TTS) makes it easy for students to exchange ideas and understand subject matter, improve student learning outcomes, and student learning completeness. After being given learning with TTS games, student learning outcomes are quite high. At the end of the second cycle, students who scored very well (or scored 80 to 100) were 7 students (64%). Students who get a score of equal to or more than 70 (KKM) are 10 students (91%). Thus, the TTS game is very effective in improving learning outcomes and student learning completeness.